2017
DOI: 10.1007/s10965-017-1296-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of aliphatic poly(ester-carbonate-urea-urethane)s potential as materials for biomedical application

Abstract: Selected mechanical and biological properties of biodegradable elastomeric poly(ester-carbonate-urea-urethane)s (PECUUs) point towards their potential to be applied as scaffolds in tissue engineering. Here we explore their medical applicability taking into account their hemocompatibility and cytotoxicity. The influence of the ester monomer (derivatives of adipic and succinic acids), as well as diisocyanate type (IPDI and HDI) on the investigated PECUUs properties is presented. The presence of aliphatic diisocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…Although proteins are highly biocompatible, their very fast degradation and low mechanical strength result in a lack of structural support during tissue development. Polymeric biomaterials are also developed by polymerizing one or more monomers either by homopolymer reaction or copolymer reaction to form non-biodegradable [ 6 , 7 ] and biodegradable materials [ 8 , 9 ]. The structure, molecular chain length, and stereochemistry can be tailored by varying chemical and physical parameters during synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Although proteins are highly biocompatible, their very fast degradation and low mechanical strength result in a lack of structural support during tissue development. Polymeric biomaterials are also developed by polymerizing one or more monomers either by homopolymer reaction or copolymer reaction to form non-biodegradable [ 6 , 7 ] and biodegradable materials [ 8 , 9 ]. The structure, molecular chain length, and stereochemistry can be tailored by varying chemical and physical parameters during synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for this situation is the biostability requirement of long-term implants and the need for revision surgery. The most important group of this type of applications are polymers [1,2,3,4]. Depending on the intended use, polymeric biomaterials may require a specific stability/degradation time.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, we have shown that PECUUs based on adipic acid derivatives are characterized by a lower glass transition temperature, higher elongation at break, and higher tensile strength compared to PECUUs containing succinate groups. Analysis of water sorption and changes in the pH of the solution after immersion tests indicates that the samples most prone to water penetration and hydrolysis were those obtained from IPDI [37]. Furthermore, the resistance of these PECUUs to biological colonization, i.e., against Candida species, as well as their hemocompatibility and lack of cytotoxicity were examined.…”
Section: Poly(urea-urethane)s Derived From Oligo(ester-carbonate) Dio...mentioning
confidence: 99%